Faktor yang Berhubungan dengan Kejadian Anemia pada Ibu Hamil - Suprayitno, Guruh; Karundeng, Jeni Oktavia; Suabey, Suningsih; Gebze, Maria Serafina (Journal of Telenursing (JOTING), 2024)
This study aims to determine what factors are related to the incidence of anemia in pregnant women at the Sota Health Center, Merauke Regency. The research method used is an analytical observational study or analytical survey with a cross-sectional research design. The study results showed a significant relationship between Compliance with Fe consumption and the incidence of anemia in pregnant women, as evidenced by a p-value of 0.001. There was no relationship between Maternal Age (p-value 0.345), Gestational Age (p-value 0.678), Education (p-value 0.699), Income (p-value 0.163), and Parity (p-value 0.911) with the incidence of anemia in pregnant women. In conclusion, of the six independent variables, 1 () factor has a relationship, namely compliance with Fe consumption, with the incidence of anemia in pregnant women. In contrast, the other five factors have no relationship with the incidence of anemia in pregnant women. Keywords: Anemia, Pregnant Women